Association between alcoholism and the dopamine D4 receptor gene. Issue 2 (February 1996) - Muramatsu, T; Higuchi, S; Murayama, M; Matsushita, S; Hayashida, M
Abstract : A point mutation in the aldehyde dehydrogenase 2 gene (ALDH2(2) allele) is considered to be a genetic deterrent for alcoholism; however, 80 of 655 Japanese alcoholics had the mutant allele. Genotype factors that might increase susceptibility by overriding the deterrent showed a higher frequency of a five repeat allele of the dopamine D4 receptor 48 bp repeat polymorphism in alcoholics with ALDH2(2) than in 100 other alcoholics and 144 controls. Alcoholics with the five repeat allele also abused other drugs more often. These data suggest the involvement of the dopamine system in the development of alcoholism and other addictive behaviour.